If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 1) + 1 + 2x = 3(2x + 2) + x Reorder the terms: 3(1 + 2x) + 1 + 2x = 3(2x + 2) + x (1 * 3 + 2x * 3) + 1 + 2x = 3(2x + 2) + x (3 + 6x) + 1 + 2x = 3(2x + 2) + x Reorder the terms: 3 + 1 + 6x + 2x = 3(2x + 2) + x Combine like terms: 3 + 1 = 4 4 + 6x + 2x = 3(2x + 2) + x Combine like terms: 6x + 2x = 8x 4 + 8x = 3(2x + 2) + x Reorder the terms: 4 + 8x = 3(2 + 2x) + x 4 + 8x = (2 * 3 + 2x * 3) + x 4 + 8x = (6 + 6x) + x Combine like terms: 6x + x = 7x 4 + 8x = 6 + 7x Solving 4 + 8x = 6 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 4 + 8x + -7x = 6 + 7x + -7x Combine like terms: 8x + -7x = 1x 4 + 1x = 6 + 7x + -7x Combine like terms: 7x + -7x = 0 4 + 1x = 6 + 0 4 + 1x = 6 Add '-4' to each side of the equation. 4 + -4 + 1x = 6 + -4 Combine like terms: 4 + -4 = 0 0 + 1x = 6 + -4 1x = 6 + -4 Combine like terms: 6 + -4 = 2 1x = 2 Divide each side by '1'. x = 2 Simplifying x = 2
| 2X^2-16X+64= | | 7y-9-4y+4=0 | | 1.2x=40.8 | | 0(2x-4)^-11/2 | | -5+x-9=15 | | -1/4a7/4a=-21 | | 3/5x-3=2.25 | | 0.4=0.75y | | -(-5-6n)-3(2n+3)=3 | | 3x+4=-2x-14 | | -12-1x=8-3x | | 5x-3y=10fory | | -6=m+(-25) | | 3x/4=2 | | 1.8q-4.3-2.3q=-1.5q-4.6 | | -6=my+(-25) | | 7x^2-21x+0=0 | | X+8+7=2x+15 | | 108=-4(-6x-3) | | -20=5+x | | 5x/6=0 | | 3(x+1)+1+2x=3(2x+2)+x | | -7(-4n-4)+2(n+5)=-22 | | (25x)/45=-65 | | 4x+12+5x=36+18x | | 35-5x=10x | | 3x=8-2(7-2x) | | -23+7+x=-19 | | U=6(8n+33)+7(n+1) | | 4y-8=2(y+6) | | 3.65x-5.26=-2.92+2.62 | | 20x^2+10x=94 |